Silver(I) coordination polymers assembled from flexible cyclotriphosphazene ligand: structures, topologies and investigation of the counteranion effects - Davarci, Derya; Gur, Rustu; Besli, Serap; Senkuytu, Elif; Zorlu, Yunus (Int Union Crystallography, 2016)
The reactions of a flexible ligand hexakis(3-pyridyloxy) cyclotriphosphazene (HPCP) with a variety of silver(I) salts (AgX; X = NO3-, PF6-, ClO4-, CH3PhSO3-, BF4- and CF3SO3-) afforded six silver(I) coordination polymers, namely {[Ag-2(HPCP)]center dot(NO3)(2)center dot H2O}(n) (1), {[Ag-2(HPCP)(CH3CN)]center dot(PF6)(2)}(n) (2), {[Ag-2(HPCP)(CH3CN)]center dot(ClO4) 2}(n) (3), [Ag-3(HPCP)(CH3PhSO3)(3)](n) (4), [Ag-2(HPCP)(CH3CN)(BF4)(2)] n (5) and {[Ag(HPCP)]center dot(CF3SO3)}(n) (6). All of the isolated crystalline compounds were structurally determined by X-ray crystallography. Changing the counteranions in the reactions, which were conducted under similar conditions of M/L ratio (1: 1), temperature and solvent, resulted in structures with different types of topologies. In complexes (1)-(6), the ligand HPCP shows different coordination modes with Ag I ions giving twodimensional layered structures and three-dimensional frameworks with different topologies. Complex (1) displays a new three-dimensional framework adopting a (3,3,6)-connected 3-nodal net with point symbol {4.6(2)}(2){4(2).6(10).8(3)}.Complexes (2) and (3) are isomorphous and have a two-dimensional layered structure showing the same 3,6L60 topology with point symbol {4.2(6)}(2){4(8).6(6).8}. Complex (4) is a two-dimensional structure incorporating short Ag center dot center dot center dot Ag argentophilic interactions and has a uninodal 4-connected sql/Shubnikov tetragonal plane net with {4(4).6(2)} topology. Complex (5) exhibits a novel threedimensional framework and more suprisingly contains twofold interpenetrated honeycomb-like networks, in which the single net has a trinodal (2,3,5)connected 3-nodal net with point symbol {6(3).8(6).1(2)}{6(3)}{8}. Complex (6) crystallizes in a trigonal crystal system with the space group R (3) over bar and possesses a three-dimensional polymeric structure showing a binodal (4,6)-connected fsh net with the point symbol (4(3).6(3))(2).(4(6).6(6).8(3)). The effect of the counteranions on the formation of coordination polymers is discussed in this study.
Keywords: cyclotriphosphazene; silver(I) coordination polymers; topological representations; counteranion